Determination of geoid heights by GPS and precise trigonometric levelling - Soycan, M (COMMONWEALTH ASSOC SURVEYING LAND ECONOMY, C A S L E, 2006)
Most commonly used method for the determination of geoid is the evaluation of GPS (Global Positioning System) and levelling measurements together. Despite the fact that geometric levelling (GL) is in general easy and practicable, it is a measurement method that is hard and uneconomic to apply particularly in mountainous, hilly and rugged areas. This study aims the use of precise trigonometric levelling (PTL) method instead of GL for the determination of precise geoid heights. The method has been probed into in consideration of the accuracy, practicability, measurement and evaluation criteria, and has been compared with GL measurement results. In addition, geoid profiles that have been determined both (GPS GL) and (GPS PTL) measurements have been compared with TG-99A (Turkish Geoid-1999A) and IGNA (Istanbul GPS Network) geoid models to explore their consistency.
Keywords: Engineering; Geology; Remote Sensing